Establishment of road network and parking lots of the UP Diliman campus VISSIM model - Rebutiaco, Carl Joshua M.; Torre, Alain Caesar N.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
With the development and initiation of the VISSIM traffic simulation model of UP Diliman, a comprehensive road and parking lot inventories are needed to further develop the existing model. This study aims to incorporate the road network and parking locations into the VISSIM model and demonstrate its use by simulation of subareas-particularly the Institute of Civil Engineering (ICE) Parking Lot Compound for the analysis of off street parking, and a portion of Quirino Avenue to analyze the effects of on-street parking (removal and pre-removal of on street parking). For the off-street parking analysis of the ICE Parking Lot Compound, the occupancy rate of the parking lot was analyzed and recommendations for the use of parking lot markings based from the measurement resulted to a capacity of 24 vehicles compared to the estimated observed value of 18 vehicles. The on-street parking analysis along Quirino Avenue resulted in decrease in travel time by 3.98 s (eastbound) and 3.89 s (westbound) and an increase in speed by 25.46% on the eastbound direction and 24.71% n the westbound direction, which conclude that removing on-street parking along Quirino Avenue will have positive effects in travel time.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Campus parking; University of the Philippines -- Parking; Traffic flow -- Simulation methods